Salvage Chemotherapy with R-DHAP in Patients with Relapsed or Refractory Non-Hodgkin Lymphoma. (13th September 2016) - Schirmbeck, Nadine G. D.; Mey, Ulrich J. M.; Olivieri, Attilio; Ko, Yon-Dschun; Kaiser, Ulrich; Flieger, Dimitri; Witzens-Harig, Mathias; Schmidt-Wolf, Ingo G. H.
ABSTRACT: This analysis reports on 72 patients with relapsed or refractory non-Hodgkin lymphoma who were treated with R-DHAP salvage chemotherapy regimen followed by high-dose chemotherapy and stem cell transplantation. The overall remission rate was 58.3%. Median time of follow-up was 28.7 months. Median progression-free survival was 29 months, estimated median overall survival was 37 months. Within a matched pair analysis these results were compared to a group that received DHAP salvage therapy without rituximab showing similar overall response rates and better estimated five-year overall survival of 59.2% versus 43.5%. R-DHAP therapy was shown to be effective and feasible with acceptable toxicity.